Job Satisfaction Differences among Coaches of Various Sports in Greece - Drakou, Αμαλία; Ηarahoussou, Υβόννη; Kabitsi, Νατάσα; Tzetzis, Γιώργος (Inquiries in Physical Education and Sport, 2008)
This study aimed to investigate sport coaches’ satisfaction in Greece among coaches of various sports. The Coach Satisfaction Scale (Drakou, 2006) was distributed to 700 coaches of 11 different sports investigating job satisfaction in nine dimensions: a) supervisor, b) nature of coaching, c) sport club’s tactics, d) colleagues, e) salary, f) coaching conditions, g) athletes’ performance, h) social dimension of coaching, and i) professional development. Football coaches had the higher level of satisfaction. Volleyball coaches and basketball coaches followed, while rhythmic gymnastics coaches, athletics coaches, rowing coaches and swimming coaches had the lowest scores. Additionally, coaches of individual sports had lower level of satisfaction compared to team sport coaches in six out of the nine dimensions. Finally, women coaches were significantly less satisfied than men coaches in seven out of the nine dimensions. The differences that arose from this research may exist because of the different organizational functions of the sport federations and the different problems due to the different nature and popularity of the sports. Further research for understanding the deeper reasons of these differences is suggested, so that these differences are studied together with concepts such as team spirit, coaching effectiveness and competition results.